2006
DOI: 10.1093/jxb/erl090
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an H+-PPase gene from Thellungiella halophila and its heterologous expression to improve tobacco salt tolerance

Abstract: An H 1 -pyrophosphatase (PPase) gene named TsVP involved in basic biochemical and physiological mechanisms was cloned from Thellungiella halophila. The deduced translation product has similar characteristics to H 1 -PPases from other species, such as Arabidopsis and rice, in terms of bioinformation. The heterologous expression of TsVP in the yeast mutant ena1 suppressed Na 1 hypersensitivity and demonstrated the function of TsVP as an H 1 -PPase. Transgenic tobacco overexpressing TsVP had 60% greater dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 36 publications
(33 reference statements)
3
92
1
Order By: Relevance
“…This may be due to the diVerence between TsVP and AVP1 or diVerent kinds of transgenic plants. Gao et al (2006) reported that the expression patterns in non-transgenic plants were diVerent between TsVP and AVP1 under salt stress. The expression of TsVP was salt induced while AVP1 was constitutively expressed, which may imply something except diVerent promoters (we have done some work, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the diVerence between TsVP and AVP1 or diVerent kinds of transgenic plants. Gao et al (2006) reported that the expression patterns in non-transgenic plants were diVerent between TsVP and AVP1 under salt stress. The expression of TsVP was salt induced while AVP1 was constitutively expressed, which may imply something except diVerent promoters (we have done some work, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…AY436553) from Thellungiella halophila (Gao et al 2006) into two cotton cultivars (Lumianyan19 and Lumianyan 21) via Agrobacterium-mediated transformation, and the transgenic cotton plants from Lumianyan19 were proved to exhibit improved salt tolerance (Lv et al 2008). Here, performance of the transgenic cotton under drought stress at three developmental stages (seedling, squaring and Xowering stages) was investigated using four transgenic lines from the two cotton genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have associated high AVP1 and SALT OVERLY SENSITIVE1 (SOS1) expression levels with increased salt tolerance (Park et al, 2005;Gao et al, 2006;Oh et al, 2009). AVP1 exist as two copies in S. parvula, with their combined expression higher than AtAVP1 (Table II).…”
Section: The Transcriptomes Of S Parvula and Arabidopsis Suggest Dismentioning
confidence: 99%
“…Genomic regions containing homologs of NHX8 , encoding a plasma membrane Li + transporter [42], and AVP1 , encoding a vacuolar proton transporter [79], were compared between T. parvula (Tp) and Arabidopsis thaliana (At). Shown are five colinear genes adjacent to NHX8 and AVP1 in the two species.…”
Section: Stress Adaptation By Gene Duplicationmentioning
confidence: 99%